MANAJEMEN KURIKULUM MERDEKA DALAM PEMBENTUKAN AKHLAK ANAK USIA DINI DI TK AL-KAUTSAR BANDAR LAMPUNG - Elia, Sukma; Dermawan, Oki; Diana, Nirva (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Independent Curriculum Management is a process or system of managing the curriculum systematically, cooperatively, comprehensively, and directed to achieve the predetermined curriculum goals. This research is a descriptive qualitative research, with data collection techniques carried out through observation, interviews, and documentation at Al-Kautsar Kindergarten related to the management of the Merdeka Curriculum in forming the morals of early childhood children, which found several results as follows: Curriculum management can be seen through several stages, namely planning, organizing, implementing and evaluating. This study is an effort to explain and analyze the management of the Independent Curriculum in shaping the morals of early childhood so that the results can contribute to the development and reference of educational management in educational institutions or agencies to be implemented and practiced, and can broaden the insights of educators related to the management of the Independent Curriculum.